A finite-element study of the effects of electrode position on the measured impedance change in impedance cardiography - Wang, Y.; Haynor, D.R.; Kim, Y. (IEEE transactions on biomedical engineering, 2001)
Traditional impedance cardiography (ICG) technique uses band electrodes both for delivering current to and measuring impedance change in the thorax. The use of spot electrodes increases the ease of electrode placement and comfort level for patients. Research has shown that changes in thoracic impedance can have multiple causes. In this study, we used finite element modeling to investigate the sources of impedance change for both band-electrode and spot-electrode ICG, and focused on how differences in electrode location affect the contribution of different sources to changes in impedance. The ultimate purpose is to identify the optimal electrode type and placement for the sensing of stroke volume (SV). Our models were built on sets of end-diastolic and end-systolic magnetic resonance images of a healthy human subject. The results showed that the effect of ventricular contraction is opposite to that of the other changes in systole: the expansion of major vessels, decrease in blood resistivity due to increased blood flow velocity, and decrease in lung resistivity due to increased blood perfusion. Ventricular contraction, the only factor that tends to increase systolic impedance, has a larger effect than any of the other factors. When spot electrodes are placed on the anterior chest wall near the heart, ventricular contraction is so dominant that the measured impedance increases from end-diastole to end-systole, and the change represents 82% of the contribution from ventricular contraction. When using the common band-electrode configuration, the change in measured impedance is a more balanced combination of the four effects, and ventricular contraction is overcome by the other three factors so that the impedance decreases. These results suggest that the belief that ICG can be used to directly measure SV based on the change in the whole thoracic impedance may be invalid, and that spot electrodes may be more useful for understanding local physiological events such as ventricular volume change. These findings are supported by previously reported experimental observations.